Current hormonal contraceptive use predicts female extra-pair and dyadic sexual behavior: evidence based on Czech National Survey data - Klapilová, Kateřina; Cobey, Kelly D; Wells, Timothy; Roberts, S Craig; Weiss, Petr; Havlíček, Jan (Evolutionary psychology, 2014)
Data from 1155 Czech women (493 using oral contraception, 662 non-users), obtained from the Czech National Survey of Sexual Behavior, were used to investigate evolutionary-based hypotheses concerning the predictive value of current oral contraceptive (OC) use on extra-pair and dyadic (in-pair) sexual behavior of coupled women. Specifically, the aim was to determine whether current OC use was associated with lower extra-pair and higher in-pair sexual interest and behavior, because OC use suppresses cyclical shifts in mating psychology that occur in normally cycling women. Zero-inflated Poisson (ZIP) regression and negative binomial models were used to test associations between OC use and these sexual measures, controlling for other relevant predictors (e.g., age, parity, in-pair sexual satisfaction, relationship length). The overall incidence of having had an extra-pair partner or one-night stand in the previous year was not related to current OC use (the majority of the sample had not). However, among the women who had engaged in extra-pair sexual behavior, OC users had fewer one-night stands than non-users, and tended to have fewer partners, than non-users. OC users also had more frequent dyadic intercourse than non-users, potentially indicating higher commitment to their current relationship. These results suggest that suppression of fertility through OC use may alter important aspects of female sexual behavior, with potential implications for relationship functioning and stability.
Keywords: Analysis of Variance; dospělí; logistické modely; zdravotnické přehledy; Female; biologická evoluce; Extramarital Relations; charakteristiky rodiny; Adult; ženské pohlaví; mladý dospělý; manželství; parita; Československo; Logistic Models; Menstrual Cycle; Adolescent; sexuální partneři; Sexual Partners; Marriage; lidé; Parity; kontraceptiva orální hormonální; Statistical Distributions; Sexual Behavior; libido; sexuální chování; Contraceptives, Oral, Hormonal; menstruační cyklus; analýza rozptylu; Age Distribution; mimomanželské vztahy; Family Characteristics; Young Adult; věkové rozložení; lidé středního věku; Libido; Health Surveys; Biological Evolution; Czechoslovakia; Middle Aged; mladiství; statistická rozdělení; Humans